Sporadic spinal psammomatous malignant melanotic nerve sheath tumor: A case report and literature review - Bonomo, Giulio; Gans, Alessandro; Mazzapicchi, Elio; Rubiu, Emanuele; Alimonti, Paolo; Eoli, Marica; Paterra, Rosina; Pollo, Bianca; Iess, Guglielmo; Restelli, Francesco; Falco, Jacopo; Acerbi, Francesco; et al. (Frontiers in Oncology, 2023)
Background. Sporadic Spinal Psammomatous Malignant Melanotic Nerve Sheath Tumor (SSP-MMNST) is a rare subgroup of peripheral nerve sheath tumors arising along the spine. Only a few reports of SSP-MMNST have been described. In this paper, we review the literature on SSP-MMNST focusing on clinical, and diagnostic features, as well as investigating possible pathogenetic mechanisms to better implement therapeutic strategies. We also report an illustrative case of a young female presenting with cervicobrachial pain due to two SSP-MMNSTs arising from C5-6 right spinal roots. Case description. We report a case of a 28-year-old woman presenting with right arm weakness and dysesthesia. Clinical examination and neuroimaging were performed, and, following surgical removal of both lesions, a histological diagnosis of SSP-MMNST was obtained. Results. The literature review identified 21 eligible studies assessing 23 patients with SSP-MMNST, with a mean onset age of 41 years and a slight male gender preference. The lumbar district was the most involved spinal segment. Gross-total resection (GTR) was the treatment of choice in all amenable cases, followed in selected cases with residual tumor by adjuvant radiotherapy or chemotherapy. The metastatic and recurrence rates were 31.58% and 36.8%, respectively. Conclusion. Differently from common schwannomas, MMNST represents a rare disease with known recurrence and metastatization propensity. As reported in our review, SSP-MMNST has a greater recurrence rate when compared to other forms of spinal MMNST, raising questions about the greater aggressiveness of the former. We also found that residual disease is related to a higher risk of systemic disease spreading. This metastatic potential, usually associated with primary lumbar localization, is characterized by a slight male prevalence. Indeed, whenever GTR is unachievable, considering the higher recurrence rate, adjuvant radiation therapy should be taken into consideration.